Deactivation of field cultivation in communal areas of South Africa: Patterns, drivers and socio-economic and ecological consequences. (March 2019) - Shackleton, C.M.; Mograbi, P.J.; Drimie, S.; Fay, D.; Hebinck, P.; Hoffman, M.T.; Maciejewski, K.; Twine, W.
Abstract: Smallholder production is a significant contributor to rural livelihoods and rural economies in much of the developing world. Yet, there is evidence of increasing disengagement in some regions, including southern Africa. However, there has been little consideration of the rates and the livelihood, ecological and policy implications of such. In this paper we examine previous studies on rates of deactivation of crop fields by smallholders in the communal areas of South Africa, supported by repeat photo images and case study material. Together these various methods show that it is a widespread phenomenon occurring at variable rates. Over short periods deactivation of crop fields can be balanced through some reactivation or intensification of homegardens. But over longer periods there is a net decline in the area of fields cultivated in many areas, with corresponding increases in the area of fallow land which, through time, may undergo changes towards more natural vegetation. We review the drivers of this deactivation of field cropping, and then contemplate the possible socio-economic and ecological implications at local and national scales. We show that there are numerous and profound implications that require greater understanding and policy responses.